The Role of The Company in The Development of The Surrounding Areas - Maulana, Iqbal; Ismiasih, Ismiasih; Kurniawati, Fitri (JURNAL AGRIBISAINS, 2024)
Regional development is an effort stage in realizing growth and change that is planned towards the modernity of society. PT. Perkebunan Nusantara (PTPN) IV as one of the oil palm plantation companies plays a role in the development of the region and surrounding communities. This research aims to determine the role of PTPN IV in the development of the area around the company. The basic method used in this research is the qualitative descriptive method. Data was collected by observation, interviews and questionnaires. Samples were taken from managers and employees totaling 30 respondents. The research results show that PTPN IV in regional development in Huta Bayu Raja District, Simalungun Regency, North Sumatra Province is in the role category with a score of 72 and is able to meet the needs of the community and employees. Regional development that has been carried out by PTPN IV includes development of production infrastructure, connecting infrastructure, socio-cultural infrastructure, public infrastructure, educational infrastructure, health infrastructure. The company needs to continue to improve physical and non-physical development to further increase its role in regional development for company employees and the surrounding community